Research and Implementation of Intelligent Home Pension System Based on Speech and Semantic Recognition. (30th March 2022) - Xie, Guokun; Hao, Sen; Zhang, Peipei; Wang, Ningning
Abstract : In order to study the current intelligent home pension system control technology, the new voice interaction technology is applied to the existing intelligent home pension system, and a multicontrol entry intelligent home pension system method is proposed. In this method, data transmission, instruction uploading, and receiving are completed by designing the communication interface of home appliance terminal to build the wireless intelligent home communication subsystem, and the voice module of IfI is adopted. The intelligent cloud is selected as the development cloud platform, and the related hardware is selected to realize the remote data communication. It has been proved that the key technology of speech recognition has been developed rapidly, the speech recognition rate has been improved (up to 97%) and the low-power speech wake up technology had breakthrough, the use of voice interaction is gradually expanding to intelligent hardware and robots, and voice interaction is undoubtedly the mainstream intelligent home pension system interaction mode after keyboard, mouse, and touch screen and also the main entrance of the future intelligent home pension system.